Education for all by 2015 : will we make it?
In 2000, over 160 countries committed to vastly expand educationalopportunities for children, youth, and adults by 2015. The sixth edition of thisglobal report marks the midterm point and provides a rich evidence-basedassessment of progress towards expanding early childhood learning programmes,reaching universal primary education, achieving gender equality at all levels ofeducation, dramatically reducing adult illiteracy, and improving educationalquality. With over 70 million children out of primary school, poor learningachievement in many countries, and 1 in 5 adults without basic literacy skills,the report stresses the dire need for innovative policies that tackle the rootcauses of exclusion, promote equity, and improve teaching and learningconditions. It also calls upon donors to step up aid to education --still afraction of total official development assistance-- in line with the promisesthey made at the turn of the century. Based on specialized commissions, extensive consultations and multiple researchsources, the report provides an authoritative, comparative reference forpolicymakers, development specialists, economists, education researchers, andadvocates worldwide.
Keywords: Education --International cooperation --Periodicals. Educational assistance -Periodicals.